THE INTERNATIONAL CRIMINAL COURT, JURISDICTION AND THE CONCEPT OF SOVEREIGNTY - Ebru Coban-Ozturk (European Scientific Journal, ESJ, 2014)
The necessity of prosecution of major crimes committed againstindividuals or groups has become a common opinion today due to theincreasing importance attached to the concept of human rights. Theinternational community demands punishing those individuals committedmajor international crimes regardless of their duties and powers. TheInternational Criminal Court has become the indicator and the outcome ofthis demand. It is a development welcomed by the majority of theinternational community in terms of an idealistic approach. However, thereare debates on the jurisdiction of the International Criminal Court. Thepowers of the Court superseding national jurisdiction and challenging theconcept of national sovereignty are the most discussed ongoing issues inparticular. The existing jurisdiction of the Court as well as the criticism ofthis jurisdiction will be discussed in this study.